PENGARUH PROFITABILITAS CAPITALTURNOVER FINANCIAL LEVERAGE KOMPOSISI ASSET UKURAN PERUSAHAAN TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA PERUSAHAAN YANG TERDAFTARDI BEI TAHUN 2019 SAMPAI 2021 - Hasian Purba (Business, Economics dan Entrepreneurship, 2022)
Based on the above problem formulation, the objectives of this study are as follows: To obtain empirical evidence on the influence of profitability, capital turnover, financial leverage, asset composition, company size, affect the tendency of accounting fraud. The type of research that will be done is a type of quantitative research that is research that obtains data in the form of numbers or qualitative data used. The population used in this study is a manufacturing company listed on the Indonesian Stock Exchange (IDX). The sample in this study is a company that has complete data that can be used to analyze profitability, capital turnover, financial leverage, asset composition, and company size. The result of the variable Return on assets (X1) has no effect on the variable Tendency of accounting fraud, variable capital turnover (X2) has no effect on the variable Tendency of accounting fraud (Y), financial leverage variable (X3) has no effect on the variable Tendency of accounting fraud (Y), asset composition variable (X4) affects the variable Tendency of accounting fraud (Y). the firm size variable (X5) has no effect on the Tendency variable of accounting fraud (Y).